Passivity of stainless steel in sulphuric acid under chemical oxidation. (3rd April 2018) - Yue, Yingying; Liu, Chengjun; Shi, Peiyang; Jiang, Maofa
ABSTRACT: The main purpose of the present work was to study the passivity of stainless steel in sulphuric acid under chemical oxidation with H2 O2 solution. Potentiodynamic polarisation and open circuit potential (OCP) measurements indicated that H2 O2 facilitates the increase of OCP of stainless steel which shifts from active region into passive region. The X-ray photoelectron spectroscopy results suggested that a passive film, composed of oxyhydroxides, Cr2 O3, Cr(VI) species, NiO, and sulphate (FeSO4, Cr2 (SO4 )3 · x H2 O), is achieved after H2 SO4 –H2 O2 passivation. The passive mechanism under H2 O2 oxidation was discussed and the corrosion resistance of passive film was compared with that of the passive films produced by HNO3 passivity and H2 SO4 potentiostatic passivity. The results of electrochemical impedance spectroscopy, cyclic voltammetry, and anodic polarisation experiments confirmed that the chemical oxidation with H2 O2 solution is capable of improving the corrosion resistance of stainless steel significantly and the passive film is more stable than those produced by other passivating methods.